Arctic and Subarctic marine heatwaves and their ecological impacts - Pecuchet, Laurene; Mohamed, Bayoumy; Hayward, Alexander; Alvera-Azcárate, Aida; Dörr, Jakob; Filbee-Dexter, Karen; Kuletz, Katherine J.; Luis, Kelly; Manizza, Manfredi; Miller, Charles E.; Staehr, Peter A. U.; Szymkowiak, Marysia; et al. (Frontiers in Environmental Science, 2025)
The Arctic and Subarctic seas are predicted to become hotspots for marine heatwaves (MHWs). High-latitude marine ecosystems face unique consequences from accelerated warming and sea ice loss, challenging species adapted to cold conditions. We review the literature on MHW characteristics and ecological impacts in the Arctic and Subarctic seas, and contrast MHW characteristics between the Bering Sea and Barents Sea. We uncover the pervasive impacts of MHWs across widely different organism groups, including benthic foundation species, phytoplankton, zooplankton, fish, seabirds, and marine mammals. MHWs in the Arctic marginal seas are especially prevalent in areas experiencing sea ice retreat, such as seasonal sea ice zones, highlighting the complex interplay between MHWs and sea ice dynamics. Overall, few studies have documented the ecological impacts of MHWs on high-latitude ecosystems, with the notable exception of the impacts from the Bering Sea and Chukchi Sea MHWs in 2017–2019. Many Arctic species, with their cold and narrow thermal preferences, appear vulnerable to MHWs, as they might not have access to cold climate refugia, while boreal species appear to benefit from Arctic and Subarctic MHWs. Sessile foundation species, such as kelp and seagrasses, are especially at risk during MHWs, although in the Arctic evidence of MHWs impacts remains limited. Reproductive failure and mass mortality events have been documented for several species in the Pacific Arctic (e.g., seabirds, fish, crabs). MHWs have been observed to have ecosystem-wide repercussions in the northern Bering Sea and Chukchi Sea with shifts in plankton communities affecting the entire food web. The ecological responses to MHWs in the Arctic and Subarctic ecosystems are still not fully understood, highlighting a need for further research to assess the direct and indirect impacts on various taxa and to improve predictive models for better management and conservation strategies. MHWs can also have large consequences for ecosystem services and socio-ecological systems, for example, closures of economically valuable and culturally important fisheries, as seen in Alaska, degradation of traditional ice-hunting practices, and compromised wellbeing of coastal communities. Large and abrupt ecosystem changes following MHWs underscore the urgent need for adaptive management strategies in the face of ongoing climate change.